Renal Evaluation of Aotus azarai infulatus by Ultrasonography and Serum Chemistry Profile - De Miranda Lins e Lins, Fernanda Luiza; Barros Monteiro, Frederico Ozanan; Cicalise Takeshita, Rafaela Sayuri; da Silva, Gilmara Abreu; Faturi, Cristian; Correia Palha, Maria das Dores; Barros Monteiro, Maria Vivina; Coutinho, Leandro Nassar; Kugelmeier, Tatiana; Gomes de Castro, Paulo Henrique (Wiley-Blackwell, 2012)
This study aimed to characterize anatomical and biochemical properties of owl monkey kidneys in order to provide normal reference values. Sixty-nine Aotus azarai infulatus (45 males and 24 females) were divided into four different age groups (AG1: 3 months1 year; AG2: 23 years; AG3: 46 years; and AG4: over 7 years old). The monkeys were evaluated with a serum chemistry profile, focusing on serum creatinine (SCr) and blood urea nitrogen (BUN) and with ultrasound. Mean body mass differed among the age groups. This significance was attributed to AG1 body mass being significantly lower than in AG2 and that in both AG2 and AG3 being significantly lower than in the two older age groups (AG3 and AG4). SCr and BUNconcentrations differed significantly between the sexes and SCr level correlated positively with age. In contrast, renal measurements did not differ between males and females. Left and right renal volumes did not differ significantly within age groups, or among AG2, AG3, and AG4. Renal volumes in AG1, however, while not differing from those in AG2, did differ significantly from those in AG3 and AG4. In conclusion, this study provides ultrasonographic reference values for the morphology the kidneys in A. a. infulatus. Evidence is also provided that SCr and BUNlevels in owl monkeys are influenced by the sex and age of the individual, factors that should be considered when interpreting test results. Am. J. Primatol. 74:482-490, 2012. (c) 2012 Wiley Periodicals, Inc.
Keywords: Aotus azarai; kidney; ultrasound; serum chemistry